Programmed increases in LXRα induced by paternal alcohol use enhance offspring metabolic adaptation to high-fat diet induced obesity - Richard C. Chang; Kara N. Thomas; Yudhishtar S. Bedi; Michael C. Golding (Elsevier, 2019)
Objectives: Paternally inherited alterations in epigenetic programming are emerging as relevant factors in numerous disease states, including the growth and metabolic defects observed in fetal alcohol spectrum disorders. In rodents, chronic paternal alcohol use induces fetal growth restriction, as well as sex-specific alterations in insulin signaling and lipid homeostasis in the offspring. Based on previous studies, we hypothesized that the observed metabolic irregularities are the consequence of paternally inherited alterations liver x receptor (LXR) activity. Methods: Male offspring of alcohol-exposed sires were challenged with a high-fat diet and the molecular pathways controlling glucose and lipid homeostasis assayed for LXR-induced alterations. Results: Similar to findings in studies employing LXR agonists we found that the male offspring of alcohol-exposed sires display resistance to diet-induced obesity and improved glucose homeostasis when challenged with a high-fat diet. This improved metabolic adaptation is mediated by LXRα trans-repression of inflammatory cytokines, releasing IKKβ inhibition of the insulin signaling pathway. Interestingly, paternally programmed increases in LXRα expression are liver-specific and do not manifest in the pancreas or visceral fat. Conclusions: These studies identify LXRα as a key mediator of the long-term metabolic alterations induced by preconception paternal alcohol use. Keywords: Epigenetic programming, Liver X receptor, Nuclear receptor, Insulin signaling, Inflammation, Paternal alcohol exposure, Metabolic programming, Preconception, Developmental origins of adult disease